Investigation of the frequency and distribution of Pychiatric comorbidities in patients with Mastalgia - Süleyman Dönmezdil; Eşref Araç; İlhan Taş; Murat Yalçın; Abidin Tüzün (Asian Journal of Medical Sciences, 2020)
Background: Mastalgia defines pain that is located in or felt in the breast area. Pain can be a symptom in many psychiatric disorders. Therefore, considering the psychiatric disorders in the evaluation of patients with mastalgia is of great importance in terms of treatment success and pain control